Japan’s Muslim-Friendly Tourism in The View of Maqasid Sharia Dharuriyah - Srifauzi, Aulia; Surwandono, Surwandono (Dauliyah: Journal of Islam and International Affairs, 2023)
Japan is a Muslim minority country but intensively promotes halal or Muslim-friendly tourism with the slogan "Yokosho Japan," which means welcome to Japan, as an invitation to travel to Japan. Several researchers consider that Muslim-friendly tourism in Japan has not shown seriousness and has become a debate whether the Muslim-friendly concept in Japan has a fundamental basis in Islam or only as a strategy to strengthen the economy and build Muslim-friendly branding in foreign eyes. This qualitative research uses the view of maqasid shariah dharuriyah to examine Muslim-friendly tourism in Japan with indicators from the Global Muslim Travel Index (GMTI) as comparison material. The study's results found that Muslim-friendly governance in Japan still ignores the principles of maqasid shariah dharuriyah. The tiny Muslim population is Japan's weakness in implementing these principles. Using content analysis, in the view of maqasid shariah dharuriyah Japan does not yet have sufficient standards to become a Muslim-friendly country.